Modelling of Oblique Wire Cutting and Experimental Application on Soft Solid Foods for the Investigation of Friction Behaviour - Tilman Witt; Yannic Holländer; Sven Tietze; Jens-Peter Majschak (Journal of Food Quality)
The sales value of ready-made foods is determined to a large extent by the appearance of the individual pieces or slices. Breakouts or deformations are perceived negatively and should be avoided. The quality of the cut surface is derived as an evaluation criterion from the evaluation of the cutting force curve. This study examines the influence of friction during cutting. The method developed for this purpose deals with the problem of separating friction from breaking and deforming when cutting with wire. To test the theoretical approach, cutting experiments with thin wires are carried out on various foodstuffs. When cutting with obliquely oriented wire, force value curves are recorded in the feed direction and perpendicular to the feed direction. The cutting force curves are reduced to two characteristic values for the active unit depending on the cross-section geometry. In connection with the result values, an explanatory model is proposed with which a quantified statement on the proportion of friction during the cut is possible. The enhanced model elucidation by oblique cutting will be helpful for the comparison of cutting tools and for the verification of computer simulations.